Impact of Advancements in Technology on Performance of the Banking Sector in New Delhi (India) - Srivastava, Karan (Digital Repository of Theses, 2025)
A business has to have a superior value delivery system and a more competitive value position. On the same ground a bank’s performance depends on how successfully it executes its service innovation to open up new markets because many innovation efforts entail introducing new services, growing current ones, and/or enhancing the service method of delivery. These days, electronic-banking provided by the banks may be used for all banking operations, including creating a new account, reviewing the balance, transferring funds, making cash deposits or withdrawals, paying bills online, purchasing insurance or other financial products, and more. The technology is available around-the-clock, allowing customers to conveniently do a variety of banking operations with a single click. Customer service made possible by I.T. has slowed down the line at the bank’s deposit and withdrawal kiosks. The present research aimed to find out how customers feel about using IT-enabled customer service. The present study found that Clients of public sector banks have the same preferences when it comes to ATMs as clients of private sector banks, according to reports. Factors such as time, location, cost, comfort, security, and user-friendliness impact the choices of both public and private bank clients when it comes to ATMs, according to the data. It has been noted that public sector bank consumers’ preferences for Internet banking are identical to those of private sector bank customers. Both public and private sector bank clients’ preferences for telebanking are influenced by factors including cost, accessibility, simplicity of use, security, and convenience. When compared to private sector bank customers, public sector bank customers have somewhat different tele-banking preferences. This research would be useful for the banking industry as it would reduce operational expenses and bank traffic since fewer consumers would need to visit the bank for various services. The survey would also help bank managers determine which demographic groups are most likely to use IT-enabled consumer services. In terms of customer happiness and quality, the study will contribute to the development of more customer-centric IT-enabled customer services. Examining how these interactions with clients might improve customers’ perceptions of quality and satisfaction will be beneficial.